Delivering person-centred holistic care for older people. (12th June 2017) - Beech, Roger; Ong, Bie Nio; Jones, Sue; Edwards, Vicky
Abstract : Purpose: This paper is an evaluated case study of the Wellbeing Coordinator (WBC) service in Cheshire, UK. WBCs are non-clinical members of the GP surgery or hospital team who offer advice and support to help people with long-term conditions and unmet social needs remain independent at home. The paper aims to discuss this issue. Design/methodology/approach: A mixed method design assessed the outcomes of care for recipients and carers using interviews, diaries and validated wellbeing measures. Service utilization data, interviews and observations of WBC consultations enabled investigation of changes in processes of care. Data were analysed using simple descriptive statistics, established instrument scoring systems and accepted social science conventions. Findings: The WBC complements medical approaches to supporting people with complex health and social care problems, with support for carers often a key service component. Users reported improvements in their wellbeing, access to social networks, and maintenance of social identity and valued activities. Health and social care professionals recognized the value of the service. Practical implications: The WBC concept relieves the burden on health and social care professionals as the social elements of ill-health are addressed. A shift in thinking from ill-health to wellbeing means older people feel more able to regain control over their own lives, being less dependent on consulting professionals. Originality/value: The WBC is a new service focussing on the individual in their health, social and economic context. Process and outcomes evaluations are rare in this field.